COVID‐19 and renin‐angiotensin system inhibition: role of angiotensin converting enzyme 2 (ACE2) ‐ Is there any scientific evidence for controversy?. (8th June 2020) - Aleksova, A.; Ferro, F.; Gagno, G.; Cappelletto, C.; Santon, D.; Rossi, M.; Ippolito, G.; Zumla, A.; Beltrami, A. P.; Sinagra, G.
Abstract: Renin–angiotensin system (RAS) blockers are extensively used worldwide to treat many cardiovascular disorders, where they are effective in reducing both mortality and morbidity. These drugs are known to induce an increased expression of angiotensin‐converting enzyme 2 (ACE2). ACE2 acts as receptor for the novel SARS coronavirus‐2 (SARS‐CoV‐2) which raising the important issue of possible detrimental effects that RAS blockers could exert on the natural history and pathogenesis of the coronavirus disease‐19 (COVID‐19) and associated excessive inflammation, myocarditis and cardiac arrhythmias. We review the current knowledge on the interaction between SARS‐CoV‐2 infection and RAS blockers and suggest a scientific rationale for continuing RAS blockers therapy in patients with COVID‐19 infection. Abstract :